In Situ/Operando Spectroscopic Characterizations Guide the Compositional and Structural Design of Lithium–Sulfur Batteries. Issue 6 (26th September 2019) - Tian, Jing‐Hua; Jiang, Tao; Wang, Mengfan; Hu, Zhongli; Zhu, Xingyu; Zhang, Li; Qian, Tao; Yan, Chenglin
Abstract: Lithium–sulfur batteries have gained incredible increasing attention due to their high theoretical energy density and comparable low cost. Although great advances are made in optimizing Li–S batteries via rational design of the composition and architecture, daunting challenges remain to restrain the shuttle‐effect issue associated with the extremely complicated "solid‐liquid‐solid" reaction routes. In recent years, researchers have reached a consensus that the characterization of practical working mechanisms of Li–S batteries is an important prerequisite for optimizing their performance. Numerous in situ/operando spectroscopic techniques with light sources of 10 −10 –10 3 m wavelengths, such as X‐rays, UV–vis, nuclear magnetic resonance (radio), infrared, etc., are introduced to supply real‐time and console‐displayed signals related to the reaction variations of Li–S batteries, thus helping to put forward further optimization strategies in the internal designs. This review systematically summarizes the state‐of‐the‐art in the optimal design of Li–S batteries with the aid of in situ/operando spectroscopic characterizations, including the progress in cathodes, binders, interlayers, electrolytes, and Li metal anodes, aiming to show the powerful ability of in situ/operando spectroscopic techniques in revealing the working and degradation mechanism and scientifically guiding the further optimal design of Li–S batteries. Abstract : Recent advances in representative in situ/operando spectroscopic techniques and their applications in guiding the compositional and structural design of Li–S batteries are systematically summarized. Case studies on sulfur cathodes, binders, interlayers, electrolytes, and lithium metal illustrate how in situ/operando spectroscopies help to understand the degradation mechanism and then scientifically guide the further optimal design of Li–S batteries.